Optical Receiver IC for CD/DVD/Blue-Laser Application - Sturm, Johannes; Leifhelm, Martin; Schatzmayr, Harald; Groiss, Stefan; Zimmermann, Horst (Design, Automation and Test in Europe, 2005)
In this paper an optoelectronic receiver IC for optical data storage applications is presented. The IC was developed in a 0.5μm BiCMOS technology with integrated PIN-photodiodes. It includes a new architecture of high-speed and low-noise transimpedance amplifiers with a gain range of 130 Ω to 270 kΩ programmable with a serial interface. The bandwidth is 260 MHz for highest gain which gives a gain-bandwidth-product of 70 THzΩ and a sensitivity improvement by a factor of 2 compared to published OEICs. The amplifiers support a special write/clip mode. The output buffers are 130 Ω impedance matched for optimized data transmission over a flex cable.